PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LEARNING TOURNAMENT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN LUBUK SIKAPING - Irfan, Irfan; Febriana, Rina; Lovia, Lita (Pendidikan Matematika, 2014)
ABSTRACTÂ The background of this research is motivated by the students understanding of mathematical concepts are still low and the responsibility of students who lack the given task during the learning process takes place. The study aims to determine whether the student understanding of mathematical concepts with application of active learning strategies Learning Tournament type better than the students understanding of mathematical concepts that apply conventional teaching eighth grade students MTsN Lubuk Sikaping. This type of research is experimental research , the design of randomized trials on the subject. Research instrument is a test of understanding of mathematical concepts. Form of the test used is in narrative form with 0,852 test reliability. The data analysis technique used is the one party t test . Based on the hypothesis test results obtained ttabel = 1.6685 and thitung = 2.966 . Hypothesis was accepted because t_hitung > ttabel, so that the hypothesis is accepted at significance level Î± = 0.05 . Could be concluded that the students understanding of mathematical concepts with application of active type of strategies Learning Tournament pembelajran better understanding of the mathematical concepts with conventional learning students in class VIII MTsN Lubuk Sikaping.